Mesenteric granulomas independently predict long‐term risk of surgical recurrence in Crohn's disease. (23rd August 2019) - Unger, L. W.; Argeny, S.; Stift, A.; Yang, Y.; Karall, A.; Freilinger, T.; Müller, C.; Bergmann, M.; Stift, J.; Riss, S.
Abstract: Aim: The risk factors that predict surgical recurrence in Crohn's disease (CD) remain controversial. Postoperative anti‐tumour necrosis factor (anti‐TNF) therapy might lower recurrence rates whilst the presence of mesenteric granulomas has been postulated to increase the risk. We hypothesized that mesenteric granulomas indicate disease severity and might predict the risk of surgical recurrence, irrespective of immunosuppressive therapy. Method: We performed a retrospective review of all consecutive patients undergoing operations for CD between January 2000 and December 2014 at a single tertiary referral centre and assessed the perioperative factors and histological findings at the time of surgery. Surgical recurrence rates and the immunosuppressive regimen were assessed through retrospective chart review and telephone interviews. Results: A total of 274 patients were eligible for analysis. Median follow‐up was 8.54 (5.48–14.42) years. A total of 63 patients (23.0%) underwent surgery for recurrent CD after a median of 4.75 (2.10–7.96) years. In final histology, 35 (12.8%) patients had mesenteric granulomas. TNF inhibitors were administered postoperatively in 104 (38.0%) and thiopurines in 137 (50.0%) patients. In univariate analysis, only the presence of mesenteric granulomas [hazard ratio (HR) 1.95; 95% CI 1.05–3.62; P  = 0.035] significantly increased the risk for recurrent surgery while postoperative anti‐TNF (HR 0.85; 95% CI 0.49–1.50; P  = 0.581) or thiopurine therapy (HR 1.03; 95% CI 0.61–1.73; P  = 0.916) did not. In multivariate analysis, only the presence of mesenteric granulomas significantly influenced the risk of surgical recurrence (HR 1.94, 95% CI 1.04–3.60; P  = 0.037). Conclusion: Intestinal and mesenteric granulomas should be differentiated in pathology reports, because mesenteric, but not intestinal, granulomas may be associated with an increased risk of surgical recurrence.